2010
DOI: 10.1021/ic1010665
|View full text |Cite
|
Sign up to set email alerts
|

Photoisomerizable Metallomesogens and Soft Crystals Based on Orthopalladated Complexes

Abstract: With the aim of obtaining light-responsive liquid-crystalline palladium complexes, six palladium complexes derived from an orthometalated imine, bearing one or two azocarboxylato bridges, have been synthesized: [Pd(2)(μ-SC(10)H(21))(μ-O(2)CAzo)(L(1,2))(2)] (7 and 8), [Pd(2)(μ-SC(10)H(21))(μ-O(2)CAzo3C(10))(L(1,2))(2)] (9 and 10), [Pd(μ-O(2)CAzo)L(1)](2) (11), and [Pd(μ-O(2)CAzo3C(10))L(1)](2) (12), in which L(1) = p-H(21)C(10)OC(6)H(3)CH═NC(6)H(4)OC(10)H(21)-p, L(2) = p-H(21)C(10)OC(6)H(3)CH═NC(14)H(29), AzoCO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 51 publications
0
12
0
Order By: Relevance
“…First, ethyl 4-aminobenzoate was diazotized with sodium nitrite to give the corresponding diazonium salt. The azo product, 4-((3,4,5-trihydroxyphenyl)­diazenyl)­benzoate ( 1 ), was obtained by reacting the freshly prepared diazonium salt with 1,2,3-tris­(hydroxybenzene) (pyrogallol) .…”
Section: Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…First, ethyl 4-aminobenzoate was diazotized with sodium nitrite to give the corresponding diazonium salt. The azo product, 4-((3,4,5-trihydroxyphenyl)­diazenyl)­benzoate ( 1 ), was obtained by reacting the freshly prepared diazonium salt with 1,2,3-tris­(hydroxybenzene) (pyrogallol) .…”
Section: Results and Discussionmentioning
confidence: 99%
“…The azo product, 4-((3,4,5-trihydroxyphenyl)diazenyl)benzoate (1), was obtained by reacting the freshly prepared diazonium salt with 1,2,3-tris(hydroxybenzene) (pyrogallol). 26 1 H nuclear magnetic resonance (NMR) showed that substitution predominantly took place at the 4-position of pyrogallol due to the electron-donating nature of the hydroxy groups, favoring substitution at the ortho and para positions. 27 Alkylation of the phenolic hydroxy groups with 11-bromo-1-undecene yielded tris-alkene ester 2, which was hydrolyzed with aqueous potassium hydroxide, followed by acidification with aqueous hydrochloric acid to give photoswitchable acid Azoac.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Actually, photo‐induced isothermal phase transitions in macroscopic order by azobenzene derivatives have been investigated for liquid crystalline to isotropic phase transition,1 crystal to isotropic phase transition,2 fluidity change in Langmuir films,3 and sol‐gel transition 4. However, photoisomerization of azobenzene is basically difficult in highly ordered crystalline solids owing to insufficient free volume; only a limited number of examples have been reported in specific conditions, such as soft crystals,5 micro crystals,6 crystal surfaces,7 nanosized crystals,8 and crystalline cyclic molecules 2. In addition, transition from a solid to a fluidic liquid with photoisomerization has rarely been reported, even in a photoisomerizable glassy solid or polymer matrices 9.…”
Section: Methodsmentioning
confidence: 99%
“…It should be noted that peak 2 is significantly lower and that peak 3 grows slightly. The changes in spectra correspond to the isomerization of trans- ACA to cis -ACA. , The UV-irradiated solution was then irradiated by visible light. The resulting spectrum is essentially the same as the fresh spectrum, indicating that cis -ACA reverted to trans- ACA.…”
Section: Resultsmentioning
confidence: 99%